2021
DOI: 10.1177/19375867211004241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biophilic Nature Imagery on Indexes of Satisfaction in Medically Complex Physical Rehabilitation Patients: An Exploratory Study

Abstract: Objective: Exposure to nature has been shown to influence various dimensions of human experience in the healthcare environment. This mixed method study explores the effects of the presence of biophilic, nature-based imagery on patient perceptions of their hospital room and aspects of their experience in rehabilitation. Background: In settings where patients have high degrees of medical acuity and infection control is a major concern, exposure to the benefits of real nature may be precluded. This is also true i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
5
0
3
Order By: Relevance
“…Moreover, the dimensions used in the present research (i.e., green items, natural light, self-rated mental health value, and satisfaction) and their significant relationships were shown to be critical drivers of patients' loyalty that has not been previously investigated. Our findings are consistent with studies that highlight that green spaces within a healthcare setting are important drivers of patient satisfaction (e.g., [39,41,76]) or loyalty (e.g., [33,77]). From a practical point of view, our findings can be utilized by healthcare managers to implement efficient biophilic design strategies within healthcare establishments that contribute to increasing patients' self-rated mental health value, which in turn determine an increase of their satisfaction with medical care and loyalty toward the healthcare provider.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the dimensions used in the present research (i.e., green items, natural light, self-rated mental health value, and satisfaction) and their significant relationships were shown to be critical drivers of patients' loyalty that has not been previously investigated. Our findings are consistent with studies that highlight that green spaces within a healthcare setting are important drivers of patient satisfaction (e.g., [39,41,76]) or loyalty (e.g., [33,77]). From a practical point of view, our findings can be utilized by healthcare managers to implement efficient biophilic design strategies within healthcare establishments that contribute to increasing patients' self-rated mental health value, which in turn determine an increase of their satisfaction with medical care and loyalty toward the healthcare provider.…”
Section: Discussionsupporting
confidence: 91%
“…A partir de 17 pesquisas relacionando ambientes restauradores e contextos de saúde, foi possível observar que os Estados Unidos são responsáveis pela maioria (n = 9) das publicações (GAO; ZHANG, 2021; MIHANDOUST et al, 2021;MODY;SUESS;DOGRU, 2019;NEJATI et al, 2015;NEJATI;RODIEK;SHEPLEY, 2016;NEZAMDOOST;NEZHAD, 2019;RAJ et al, 2022;SCATES et al, 2020;WICHROWSKI et al, 2021). O Brasil, por sua vez, é o país de origem de 5 estudos sobre a temática (BOCCANERA; BOCCANERA; BARBOSA, 2006;CAMPAGNOL;SHEPLEY, 2014;FELIPPE et al, 2020;SEVERO, 2005;SIQUEIRA et al, 2019).…”
Section: Resultados Incidência De Pesquisasunclassified
“…Patient satisfaction is defined as ''the perception and overall evaluation of the medical service quality, as well as patients' judgments regarding the process of medical treatment'' (Lu et al, 2021). Previous research has found that physical attributes of healthcare setting are significant predictors of patient satisfaction (e.g., Wichrowski et al, 2021). Specifically, healthcare environments that are perceived as comfortable, safe, and pleasing are likely to be rated more highly by patients, which increases their satisfaction (Sadler et al, 2011).…”
Section: Relationships Among Mental Health Value Emotional Wellbeing ...mentioning
confidence: 99%
“…They found that physical attributes, such as interior design, ambient environment, presence of artwork, window views of nature, and adequate lighting are classified as a source of overall satisfaction. Other studies indicated that patients who stay in hospital rooms with natural/green features are more satisfied with their rooms than those who stay in rooms without such features (Park & Mattson, 2009; Wichrowski et al, 2021). As patients are becoming increasingly concerned with and are more critical of the healthcare provided, satisfying them and complying with their needs should become an important target for every healthcare establishment.…”
Section: Literature Reviewmentioning
confidence: 99%